Metabolic Syndrome and Efficacy of Remote Ischemic Postconditioning in Acute Moderate Ischemic Stroke: A Post Hoc Analysis of the RICAMIS Trial - Yi‐Na Zhang; Qiong Wu; Yu Cui; Nan‐Nan Zhang; Hui‐Sheng Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Metabolic syndrome (METS) is associated with poor outcomes after acute ischemic stroke. This study aimed to investigate the relationship between METS and efficacy of remote ischemic postconditioning (RIPostC) in acute moderate ischemic stroke using the database of the RICAMIS (Remote Ischemic Conditioning for Acute Moderate Ischemic Stroke) trial. Methods and Results In the RICAMIS trial, eligible participants were patients with acute moderate ischemic stroke within 48 hours of onset who did not receive reperfusion treatment. A total of 1482 patients were enrolled in this secondary analysis, including the METS (602) and non‐METS (880) group according to the METS definitions of the Chinese Diabetes Society, which was further subdivided into RIPostC and control subgroups. The primary outcome was excellent functional outcome, defined as a modified Rankin Scale score of 0 to 1 at 90 days. The differences in clinical outcomes between the RIPostC subgroup and control subgroup were compared in patients with METS or non‐METS, respectively, and the interaction effects of RIPostC treatment assignment with METS status were evaluated. The baseline characteristics between RIPostC and control subgroups across patients with METS and non‐METS were well balanced, except the difference in Trial of Org 10 172 in Acute Stroke Treatment stroke mechanism in the METS group. Compared with control, RIPostC was associated with high probability of excellent functional outcome in patients with METS (68.8% versus 56.1%; odds ratio [OR], 1.751 [95% CI, 1.248–2.456]; P=0.001), but not in patients without METS (66.6% versus 64.6%; OR, 1.103 [95% CI, 0.833–1.461]; P=0.494). Notably, a significant interaction effect between treatments (RIPostC or control) by different METS status on excellent functional outcome was observed (P=0.039). Conclusions The secondary analysis suggests for the first time that RIPostC may provide greater benefit in patients with acute ischemic stroke with METS versus non‐METS.